The Relationship Between the Participatory Management and the School Effectiveness Under the Secondary Educational Service Area Office Bangkok 2 - Hirantrakul, Laksanich; Indusuta, Kanyamon (Executive Journal, 2025)
The objectives of this research were to: 1) study the participatory management under the Secondary Educational Service Area Office Bangkok 2, 2) study school effectiveness under the Secondary Educational Service Area Office Bangkok 2, and 3) study the relationship between participatory management and school effectiveness under the Secondary Educational Service Area Office Bangkok 2. The sample group, selected using multi-stage random sampling, consisted of 357 secondary school teachers in the academic year 2024. The research instrument was a questionnaire on the relationship between participatory management by school administrators and school effectiveness, with a reliability coefficient of 0.989. The statistics used for data analysis included frequency, percentage, mean, standard deviation, and Pearson’s product-moment correlation coefficient. The research findings revealed that the participative management of school administrators and the overall as well as specific aspects of school effectiveness were rated at a high level. Furthermore, there was a strong positive correlation, at a statistically significant level of 0.01, between the participative management of school administrators and the effectiveness of schools under the jurisdiction of the Secondary Educational Service Area Office Bangkok 2.